Rethinking Botanic Gardens: The Human Dimension of Nature in Selected Poems by Muhammad Haji Salleh: (Tanggapan Baharu Taman Botani: Dimensi Manusia oleh Alam dalam Puisi Pilihan Muhammad Haji Salleh) (Malay Literature, 2015)
Botanic gardens have not changed much from the day they were established until today. Generally, a botanic garden is devoted to the collection, cultivation and display of a wide range of plants. In principle, its role is to maintain a documented collection of living plants for the purpose of scientific research, conservation, display and education. However, one of the major functions of botanic gardens is being ignored, that is, to instil and generate the sense of oneness between man and nature. Basically, man is inclined to destroy nature rather than preserve it for commercial reasons. Efforts to curb this problem have not been successful. Educational programmes conducted by botanic gardens to educate visitors with scientific information regarding nature have not been adequate. They have neglected the human dimension of nature which is so important in developing a sense of oneness between man and nature. Where and how to derive the human dimension from? This paper will explore the human dimension of plants as discovered in poetry written specifically about the human dimension to reveal the closeness between man and nature. Muhammad Haji Salleh, a well-known Malaysian poet, has written poems about plants that are common in tropical botanic gardens. Textual analysis has been used to study the poems and has uncovered the human dimension in them. This discovery gives insight into a new model of botanic gardens as the manifestations of botany (science of plants) and poetry, thus providing the human dimension absent in previous models. According to this new model, then, botanic gardens have a new role to play in providing the educational programmes for the public.Keywords: poem, human dimension, botanic garden, nature